FAM134B-Mediated ER-phagy Upregulation Attenuates AGEs-Induced Apoptosis and Senescence in Human Nucleus Pulposus Cells. (6th August 2021) - Luo, Rongjin; Li, Shuai; Li, Gaocai; Lu, Saideng; Zhang, Weifeng; Liu, Hui; Lei, Jie; Ma, Liang; Ke, Wencan; Liao, Zhiwei; Wang, Bingjin; Song, Yu; et al.
Abstract : Previous studies have established the pathogenic role of advanced glycation end products (AGEs) accumulation in intervertebral disc degeneration (IDD). Emerging evidence indicates that ER-phagy serves as a crucial cellular adaptive mechanism during stress conditions. This study is aimed at investigating the role of FAM134B-mediated ER-phagy in human nucleus pulposus (NP) cells upon AGEs treatment and exploring its regulatory mechanisms. We observed that AGEs treatment resulted in significantly increased apoptosis, senescence, and ROS accumulation in human NP cells; meanwhile, the enhanced apoptosis and senescence by AGEs treatment could be partially alleviated with the classic ROS scavenger NAC administration. Furthermore, we confirmed that FAM134B-mediated ER-phagy was activated under AGEs stimulation via ROS pathway. Importantly, it was also found that FAM134B overexpression could efficiently relieve intracellular ROS accumulation, apoptosis, and senescence upon AGEs treatment; conversely, FAM134B knockdown markedly resulted in opposite effects. In conclusion, our data demonstrate that FAM134B-mediated ER-phagy plays a vital role in AGEs-induced apoptosis and senescence through modulating cellular ROS accumulation, and targeting FAM134B-mediated ER-phagy could be a promising therapeutic strategy for IDD treatment.